Solar wind interaction with Mars: electric field morphology and source terms. Issue 3 (25th January 2023) - Wang, Xiao-Dong; Fatemi, Shahab; Nilsson, Hans; Futaana, Yoshifumi; Holmström, Mats; Barabash, Stas
ABSTRACT: The correlation between space environment conditions and the properties of escaping ions is a central topic of Mars research. Although empirical correlations have been visible in the data, a physics-based interpretation, rather than statistics-based pictures, has not been established yet. As a first effort, we investigate the electric field, the direct contributor to ion acceleration, in the Mars plasma environment from a hybrid plasma model (particle ions and fluid electrons). We use Amitis, a hybrid model combined with an observation-based ionospheric model, to simulate the Mars–solar wind interaction under nominal solar wind plasma conditions for perpendicular and Parker spiral directions of the interplanetary magnetic field (IMF). The simulations show following results: (1) the electric field morphology is structured by the IMF direction and the different plasma domains in the solar wind–Mars interaction; (2) asymmetry of the electric field between the hemispheres where the convective electric field points inward and outward, respectively, due to the mass loading and asymmetric draping of the magnetic field lines; (3) the motional electric field dominates in most regions, especially in the dayside magnetosheath; and (4) the Hall term is an order of magnitude weaker and significant in the magnetotail and plasma boundaries for a perpendicular IMF case. The Hall term is relatively stronger for the Parker spiral case. (5) The ambipolar electric field, in principle, agrees with Mars Atmosphere and Volatile Evolution measurements in the magnetosheath.